2019
DOI: 10.9755/ejfa.2018.v30.i12.1884
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and prediction of genotypic values in common beans using mixed models#

Abstract: In the international scenario of agriculture, Brazil stands out as the main producer and consumer of common bean (Phaseolus vulgaris L.) The increase in the productive potential of the crop is mainly due to breeding programs. The objective of this study was to estimate genetic parameters, predict genotypic values ​​with REML/BLUP (Restricted Maximum Likelihood/Best Linear Unbiased Prediction) and, based on these values,​​ study the variability in common bean cultivars with carioca and black grain. Twenty three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The results of the individual (Table 1) and joint analyses (Table 2) showed differences among genotypes and among environments for all traits, which has been reported in other studies on common bean (Alvares et al, 2016;Corrêa et al, 2016;Delfini et al, 2018;Silva et al, 2018). Even with the previous selection of lines (Alvares et al, 2016), there was still variability among them within each population.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The results of the individual (Table 1) and joint analyses (Table 2) showed differences among genotypes and among environments for all traits, which has been reported in other studies on common bean (Alvares et al, 2016;Corrêa et al, 2016;Delfini et al, 2018;Silva et al, 2018). Even with the previous selection of lines (Alvares et al, 2016), there was still variability among them within each population.…”
Section: Resultssupporting
confidence: 74%
“…Under those conditions, analyses of adaptability and stability can assist in identifying promising lines. For grain yield in common bean, several studies have confirmed the importance of the genotype by environment interaction (Alvares et al, 2016;Corrêa et al, 2016;Delfini et al, 2018;Di Prado et al, 2019). However, works of this type are not frequent for seed-coat darkening, 100-grain weight, plant architecture, and resistance to lodging (Alvares et al, 2016;Delfini et al, 2018;Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…low Ac value obtained for YLD is a consequence of the high influence of the environment for the trait, making it difficult to select the best accessions. Delfini et al [40] estimated genetic parameters for 39 Brazilian bean cultivars and obtained a lower h 2 for YLD (0.12) than for other traits.…”
Section: Plos Onementioning
confidence: 99%
“…The absence of correlation between YLD and the other morpho-agronomic or biochemical traits is considered a complicating factor in the selection of genitors. Delfini et al [40] observed that YLD was correlated with traits related to seed morphology in black-type common bean, but with the number of seeds produced in carioca-type. These facts are related to the objectives of breeding programs in Brazil.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation